Enantioselective RP-UFLC Method for the Simultaneous Estimation of Sitagliptin (STG) enantiomers (R and S) in racemic mixture and their Pharmacokinetic assessment in male Wistar Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present work aims to develop and validate a simple, rapid, and reproducible reverse phase ultra-fast liquid chromatography method with a UV detector (RP-UFLC-UV) was developed for the separation and determination of sitagliptin (STG) enantiomers (S-(STG) and R-(STG)) simultaneously. Baseline separation was achieved on Lux cellulose-1 column, (cellulose tri-(3,5-dimethyl phenyl carbamate (Chiralcel OD-RH, 250 mm × 4.6 mm, 5 μm) column and mobile phase consisted of 20mM borate buffer solution (pH = 9±0.05) and ACN in the ratio of (60:40, v/v) at a flow rate of 0.8 mL/min was used. Detection of peaks was monitored at 262 nm. For analyzing the STG enantiomers in the rat serum and pure API, a method was developed using the chiral RP-UFLC-UV method was validated. The single oral dose of 2.5 mg/kg of STG racemate was administered to a group of 6 healthy rats for a comparative pharmacokinetic study of both the enantiomers. The linear range of the calibration curve for each enantiomer was 0.5–64 μg/mL. The precision of this method at concentrations between 0.5–48 μg/mL was within 8.65% and the % recovery (accuracy) of both sitagliptin (STG) enantiomers (S-(STG) and R-(STG) were 98.47–101.02% and 98.93-100.52%. The precision at LLOQ (0.5 μg/mL) was between 8.65%-7.09%, which was poor than that at QC levels, and the average extraction recovery was higher than 85% for both sitagliptin (SGT) enantiomers at QC levels, and its pharmacokinetics of enantiomers was found to be stereoselective.